A Mach-Zehnder interferometer electro-optic switch with ultralow voltage-length product using poled-polymer/silicon slot waveguide - 黄小亮 李翠婷 党佩佩 郑传涛 (Optoelectronics letters, 2015)
By using poled-polymer/silicon slot waveguides in the active region and the Pockels effect of the poled-polymer,we propose a kind of Mach-Zehnder interferometer（MZI） electro-optic（EO） switch operated at 1 550 nm.Structural parameters are optimized for realizing normal switching function.Dependencies of switching characteristics on the slot waveguide parameters are investigated.For the silicon strip with dimension of 170 nm×300 nm,as the slot width varies from 50 nm to 100 nm,the switching voltage can be as low as 1.0 V with active region length of only 0.17–0.35 mm,and the length of the whole device is only about 770–950 μm.The voltage-length product of this switching structure is only 0.17–0.35 V·mm,and it is at least 19–40 times smaller than that of the traditional polymer MZI EO switch,which is 6.69 V·mm.Compared with our previously reported MZI EO switches,this switch exhibits some superior characteristics,including low switching voltage,compact device size and small wavelength dependency.